Evolution of nMOFs in photodynamic therapy: from porphyrins to chlorins and bacteriochlorins for better efficacy - Zou, Yutao; Chen, Jiayi; Qu, Yijie; Luo, Xuanxuan; Wang, Weiqi; Zheng, Xiaohua (Frontiers in Pharmacology, 2025)
Photodynamic therapy (PDT) has gained significant attention due to its non-invasive nature, low cost, and ease of operation. Nanoscale metal-organic frameworks (nMOFs) incorporating porphyrins, chlorins, and bacteriochlorins have emerged as one of the most prominent photoactive materials for tumor PDT. These nMOFs could enhance the water solubility, stability and loading efficiency of photosensitizers (PSs). Their highly ordered porous structure facilitates O2 diffusion and enhances the generation of 1O2 from hydrophobic porphyrins, chlorins, and bacteriochlorins, thereby improving their efficacy of phototherapy. This review provides insights into the PDT effects of nMOFs derived from porphyrins, chlorins, and bacteriochlorins. It overviews the design strategies, types of reactive oxygen species (ROS), ROS generation efficiency, and the unique biological processes involved in inhibiting tumor cell proliferation, focusing on the mechanism by which molecular structure leads to enhanced photochemical properties. Finally, the review highlights the new possibilities offered by porphyrins, chlorins, and bacteriochlorins-based nMOFs for tumor PDT, emphasizing how optimized design can further improve the bioapplication of porphyrin derivatives represented PSs. With ongoing research and technological advancements, we anticipate that this review will garner increased attention from scientific researchers toward porphyrin-based nMOFs, thereby elevating their potential as a prominent approach in the treatment of malignant tumors.